Database Management System Using Index efiltering In Information Retrival System (International Journal of Engineering and Computer Science, 2017)
A database management system (DBMS) is a software package with computer programs that control the creation, maintenance, and use of a database. It allows organizations to conveniently develop databases for various applications by database administrators (DBAs) and other specialists. Information retrieval emerged as independent research area from traditional database management system more than a decade ago. This was driven by the increasing functional requirements that modern full text search engines have to meet. Current database management systems (DBMS) are not capable of supporting such flexibility. However, with the increase of data to be indexed and retrieved and the increasing heavy workloads, modern search engines suffer from Scalability, reliability, distribution and performance problems. We present a new and simple way for integration and compare the performance of our system to the current implementations based on storing the full text index directly on the file system.